2021
DOI: 10.3390/foods10030485
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Enzymatically Treated Apple Pomace from Juice Production by Extrusion Processing

Abstract: Food by-products can be used as natural and sustainable food ingredients. However, a modification is needed to improve the technofunctional properties according to the specific needs of designated applications. A lab-scale twin-screw extruder was used to process enzymatically treated apple pomace from commercial fruit juice production. To vary the range of the thermomechanical treatment, various screw speeds (200, 600, 1000 min−1), and screw configurations were applied to the raw material. Detailed chemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
(64 reference statements)
5
7
0
Order By: Relevance
“…A distinct decrease in galactose contents was only found for the sample that was treated at 160 °C and 40% water content. These results are consistent with previous studies stating that arabinose and galacturonic acid portions in IDF of apple pomace decrease under thermomechanical stress [3,17]. Also, studies on chokeberry pomace that was treated by using a CCR showed that under various thermal effects arabinose and galacturonic acid containing pectic polymers are most prone to degradation [22].…”
Section: Monosaccharide Composition and Glycosidic Linkages Of Dietary Fiber Poly-and Oligosaccharidessupporting
confidence: 92%
See 3 more Smart Citations
“…A distinct decrease in galactose contents was only found for the sample that was treated at 160 °C and 40% water content. These results are consistent with previous studies stating that arabinose and galacturonic acid portions in IDF of apple pomace decrease under thermomechanical stress [3,17]. Also, studies on chokeberry pomace that was treated by using a CCR showed that under various thermal effects arabinose and galacturonic acid containing pectic polymers are most prone to degradation [22].…”
Section: Monosaccharide Composition and Glycosidic Linkages Of Dietary Fiber Poly-and Oligosaccharidessupporting
confidence: 92%
“…The largest amount of LMW-SDF was formed at a treatment temperature of 160 °C and a water content of 40% (F). These results support the findings that dietary fiber from apple pomace is susceptible to thermomechanical stress [3,17]. However, a detailed chemical interpretation of the changes of IDF, SDF, and LMW-SDF contents is difficult because these changes are most likely the result of a complex interaction: cleavage of glycosidic linkages, degradation of carbohydrate units, and the formation of high-molecular weight Maillard reaction products that are captured as dietary fiber.…”
Section: Dietary Fiber Contentssupporting
confidence: 85%
See 2 more Smart Citations
“…As a result, syneresis in food products such as deserts and sausages can be decreased or the texture of bread be improved [10]. We recently demonstrated that the functional properties of, for example, apple and chokeberry pomace are strongly affected by extrusion [10,[12][13][14]. On a polysaccharide structural level, extrusion of these food by-products mainly degraded arabinans as neutral side chains of rhamnogalacturonan I [12,13].…”
Section: Introductionmentioning
confidence: 99%